Uji Aktivitas Antijamur Ekstrak Propolis dari Lebah Trigona Sp Asal Balikpapan terhadap Candida Tropicalis - Muthia Adlina; Indah Woro Utami; Nishia Waya Meray (Pusat Riset dan Inovasi Nasional, 2025)
Fungal infections are a common health problem in tropical regions, including Indonesia, since humid conditions support microbial growth. Candida tropicalis is a pathogenic species frequently identified as the cause of both superficial and systemic candidiasis. The rising resistance to synthetic antifungal agents such as fluconazole and ketoconazole highlights the need for safer and more effective alternative therapies. Propolis, a resinous substance produced by Trigona sp. bees from various plant sources, contains flavonoids, phenolics, and terpenoids with important biological activities, including antimicrobial and antifungal effects. This study aimed to evaluate the effectiveness of ethanol extract of propolis from Balikpapan against the growth of Candida tropicalis using the disk diffusion method. Phytochemical screening revealed the presence of alkaloids, flavonoids, phenolics, tannins, and terpenoids in the extract. Antifungal activity testing showed that concentrations of 80%, 90%, and 100% significantly inhibited fungal growth, with the largest inhibition zone of 27.93 mm observed at 100% concentration. Statistical analysis using ANOVA confirmed significant differences among treatments. Thus, ethanol extract of Trigona sp. propolis from Balikpapan demonstrates strong potential as a natural antifungal agent. These findings support the use of propolis as a natural-based therapeutic alternative for fungal infections and contribute to the development of herbal pharmaceutical products.